PENINGKATAN PRODUKSI PRODUK PERIKANAN MELALUI PENERAPAN GREEN ECONOMY DI KELOMPOK MINA AYU, DESA MARGA, TABANAN, BALI - Suryani, Sang Ayu Made Putri; Edi, Dewa Gede Semara; Ningsih, Ni Luh Anik Puspa (Universitas Mataram, 2025)
The Mina Ayu group in Desa Baru, Tabanan, Bali, has significant potential in agriculture, fisheries, and tourism, particularly tilapia (Oreochromis niloticus) aquaculture supported by abundant freshwater resources. Since 2018, the community has developed tilapia hatchery production that reached wider markets; however, management remains suboptimal due to fish disease outbreaks and limited use of natural remedies. Neem (Azadirachta indica) leaves contain bioactive compounds with antibacterial, antioxidant, and immunostimulant properties, making them a promising alternative for sustainable aquaculture disease control. This program aimed to improve tilapia production and quality through neem leaf extract application, strengthen financial management, and enhance the economic independence of the Mina Ayu group. The community engagement program was conducted from August to October 2025 with 12 members of the Mina Ayu group. Methods included interviews, group discussions, lectures, training on neem extract preparation and application, field practice, and mentoring on financial management and marketing strategies. The program resulted in a significant improvement in farmers’ understanding of fish disease control and water quality management. The application of neem leaf extract in tilapia feed increased the survival rate from 60% to 100% and enhanced fish growth performance and resistance. Group members successfully produced both liquid and powdered neem extract and adopted simple financial recording tools such as daily cash books and profit–loss statements. Training also improved financial literacy, social media–based marketing, and overall business efficiency. The utilization of neem leaf extract effectively improved tilapia aquaculture performance while strengthening financial literacy, thereby supporting business sustainability and the community’s economic independence.